2009
DOI: 10.1002/ibd.20976
|View full text |Cite
|
Sign up to set email alerts
|

Quality of web-based information on inflammatory bowel diseases

Abstract: The quality of websites containing information on IBD varies widely. Most of the online material available is too difficult to comprehend for a substantial portion of the patient population, and good quality information may be beyond reach of the average information seeker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 17 publications
(27 reference statements)
10
75
2
1
Order By: Relevance
“…This finding is consistent with those of some studies 34 but not with others. [35][36][37][38] These varying results could be because very few sites have the HON label, because of the criteria used for the HON label (related more to ethical considerations than to quality), and because this label is only given if the site's Web master requests it. It is important to note that quality seals are still only used by a limited number of sites, and government sites do not use them.…”
Section: Discussionmentioning
confidence: 90%
“…This finding is consistent with those of some studies 34 but not with others. [35][36][37][38] These varying results could be because very few sites have the HON label, because of the criteria used for the HON label (related more to ethical considerations than to quality), and because this label is only given if the site's Web master requests it. It is important to note that quality seals are still only used by a limited number of sites, and government sites do not use them.…”
Section: Discussionmentioning
confidence: 90%
“…15 It has been suggested that standard text should achieve FRE scores between 60 and 70. 3,16 Statistical Analysis Data were analyzed using simple descriptive statistics. The difference between the mean DISCERN scores of Web sites by search term was analyzed using one-way analysis of variance, as was the difference between FRE scores by search term.…”
Section: Readabilitymentioning
confidence: 99%
“…Numerous sites in our study scored "low" for their reliability. Average readability score was 49.8 and less than one-fourth of sites had a readability score above 60, which is often cited as the minimum recommended for patients (Van der Marel et al 2009;D'Alessandro et al 2001). Further, nearly 40% (13/33) of sites had not been updated since January 1, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…7/33 (21.2%) websites scored above 60, the recommended range for average visitors (Van der Marel et al 2009;D' Alessandro et al 2001). 20/33 (60.6%) of sites had been updated since January 1, 2014.…”
Section: Data Collection and Analysismentioning
confidence: 98%